Broad-band terahertz metamaterial absorber with stacked electric ring resonators. Issue 7 (3rd May 2017) - Astorino, Maria Denise; Frezza, Fabrizio; Tedeschi, Nicola
Abstract: In this paper, we propose an ultra-thin broad-band metamaterial absorber composed of a periodic array of three-layered electric ring resonators (ERRs) within a dielectric spacer and backed by a metallic ground plane for THz applications. The overlapping of the resonance peaks relevant to the ERRs leads to a broad spectral absorption bandwidth over a wide range of incidence angles under both transverse electric and transverse magnetic polarizations. We analyze the effect of different physical properties on the absorption spectra in order to estimate the dielectric and Ohmic losses in the metamaterial structure. In addition, the Nicolson, Ross, and Weir algorithm is adopted as homogenization technique to retrieve the effective electromagnetic parameters, while the interference theory is employed to compare the simulated and analytical results for the multi-layered absorber.